Hombre, NoyΣ e Iusnaturalismo (2011)
The writer of this work intends to support both νοῦς and λόγος‘s genuinity, as a foundation of Natural moral Law. This genuinity may be found in infinity as a hermeneutical horizon that provides man a concept of being in universal. Some current trends of the scientific view point deny man hold this infinite element, and therefore, that kind of faculty. For that reason, the writer discusses one of them with sociobiology, which he contrasts withthe Natural Law view point of moral law.Keywords: Philosophical anthropology, ethics, νοῦς and natural law.